Persepsi dan Harpan Guru terhadap Iklim Sekolah Menengah Kejuruan Negeri (SMKN) 2 Padang - Ryan Pratama; Hadiyanto Hadiyanto; Ermita Ermita; Nelfia Adi (Journal of Educational Administration and Leadership, 2021)
The purpose of this study was to find data and information regarding teachers' perceptions and expectations of the school climate in terms of 1) support to students, 2) leadership, 3) student participation, 4) encouragement, 5) clarity of rules, 6) cooperation, 7) care for students, 8) completeness of resources. This research is a descriptive study. The population of this study were all teachers in Vocational High School 5 Padang with a total population of 100 people. This research is a population research, that is, if the subject is more than 100, it is better to use Stratified Proportional Random Sampling, namely the technique of determining the sample using the Slovin formula with the sum of 50 teachers. The research instrument is a questionnaire with a Likert scale model that has been tested for validity and reliability. The collected data were analyzed using the mean (average) formula. Teachers' perceptions and expectations of the school climate in Vocational High School 2 Padang are in the category of good enough perception with an average score of 3.4 while expectations are in the good category with an average score of 4.1.